Pengaruh Strategi Mind Mapping terhadap Peningkatan Ketrampilan Berbicara Siswa Kelas X MA Sumberkelompang Implementasi Media Majalah Santri dalam Pembelajaran Pendidikan Bahasa Indonesia - Moh. Raji; Harsono Harsono (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aimed to improve the speaking skills of tenth-grade students at MA Mambaul Ulum Sumberlompang through the implementation of the Mind Mapping strategy using the Majalah Santri (Santri Magazine) as a learning medium. The research employed a Classroom Action Research (CAR) design based on the Kemmis and Taggart model, which consisted of two cycles involving planning, action, observation, and reflection. The participants were tenth-grade students of MA Mambaul Ulum Sumberlompang. Data were collected through classroom observations, speaking performance tests, and documentation. The findings revealed that the application of the Mind Mapping strategy integrated with Majalah Santri effectively enhanced students’ participation, motivation, and speaking skills. In the pre-action stage, the average speaking skill achievement was 52.61%. After the implementation of the second cycle, the speaking skill percentage increased to 69.70%, while the average post-test score reached 89.4%. Furthermore, students demonstrated positive responses toward the learning process by showing greater self-confidence in expressing ideas, organizing thoughts systematically, and actively participating in discussions and presentations. Therefore, the integration of the Mind Mapping strategy with Majalah Santri proved to be effective in improving students’ speaking skills and fostering a more innovative, contextual, and interactive Indonesian language learning environment.